Вплив довготривалого стресу на жінок в умовах воєнного стану : кваліфікаційна робота - магістерський дослідницький проект 053 «Психологія» - Гарбут, Анна Ігорівна (Одеса : НУ «ОЮА», 2025)
Шляхом теоретико-методологічного аналізу наукових досліджень встановлено, що тривала дія стресових факторів, особливо стану війни, може погіршити психічне та фізичне здоров’я. Психологічний аспект стресу значно залежить від того, як жінки сприймають його передбачуваність і контрольованість. Встановлено наявність значимих кореляційних зв’язків різного знаку між показниками стресу і депресії та копінг-стратегіями. Доведено, що всі показники довготривалого стресу (тривожність, агресивність, депресивність) супроводжуються підвищенням неадаптивних стратегій його подолання. А інтерес і зацікавленість протистоять стресу і сприяють вибору адаптивних копінг-стратегій. Проведено якісний аналіз груп жінок з максимальним та мінімальним стресом. Встановлено, що в групі жінок з максимальним довготривалим стресом найбільш виражені такі риси як: агресивність до оточуючих, особистісна та ситуативна тривожність, стресонестійкість та депресивність. У них домінують такі копінг-стратегії як: конфронтація, втеча-уникання, дистанціювання, а не характерними стратегіями є планування рішення проблеми та позитивна переоцінка. Компоненти як фізичного, так і психічного здоров'я знижені саме в цій групі. Також у них знижені всі показники життєстійкості (прийняття ризику, контроль, залученість) та зменшені всі показники психологічного благополуччя (управління середовищем, автономія, баланс афекту, самоприйняття, позитивні відносини). На основі встановлених даних розроблено рекомендації з подолання наслідків. Through theoretical and methodological analysis of scientific research, it was established that the prolonged effect of stress factors, especially the state of war, can worsen mental and physical health. The psychological aspect of stress depends significantly on how women perceive its predictability and controllability. The presence of significant correlations of different signs between indicators of stress and depression and coping strategies has been established. It has been proven that all indicators of long-term stress (anxiety, aggressiveness, depression) are accompanied by an increase in maladaptive coping strategies. And interest and curiosity counteract stress and contribute to the choice of adaptive coping strategies. A qualitative analysis of groups of women with maximum and minimum stress was conducted. It was found that in the group of women with maximum long-term stress, the following features are most pronounced: aggressiveness towards others, personal and situational anxiety, stress instability and depression. They are dominated by such coping strategies as: confrontation, escape-avoidance, distancing, and not characteristic strategies are planning a solution to the problem and positive reappraisal. Components of both physical and mental health are reduced in this group. They also have reduced all indicators of resilience (risk taking, control, involvement) and reduced all indicators of psychological well-being (environmental management, autonomy, affect balance, self- acceptance, positive relationships). Based on the established data, recommendations have been developed for overcoming the effects of long-term stress on women under martial lawвпливу довготривалого стресу на жінок в умовах воєнного стану. Through theoretical and methodological analysis of scientific research, it was established that the prolonged effect of stress factors, especially the state of war, can worsen mental and physical health. The psychological aspect of stress depends significantly on how women perceive its predictability and controllability. The presence of significant correlations of different signs between indicators of stress and depression and coping strategies has been established. It has been proven that all indicators of long-term stress (anxiety, aggressiveness, depression) are accompanied by an increase in maladaptive coping strategies. And interest and curiosity counteract stress and contribute to the choice of adaptive coping strategies. A qualitative analysis of groups of women with maximum and minimum stress was conducted. It was found that in the group of women with maximum long-term stress, the following features are most pronounced: aggressiveness towards others, personal and situational anxiety, stress instability and depression. They are dominated by such coping strategies as: confrontation, escape-avoidance, distancing, and not characteristic strategies are planning a solution to the problem and positive reappraisal. Components of both physical and mental health are reduced in this group. They also have reduced all indicators of resilience (risk taking, control, involvement) and reduced all indicators of psychological well-being (environmental management, autonomy, affect balance, self- acceptance, positive relationships). Based on the established data, recommendations have been developed for overcoming the effects of long-term stress on women under martial law.
Гарбут А. І. Вплив довготривалого стресу на жінок в умовах воєнного стану : кваліфік. робота - магістер. дослідн. проєкт 053 «Психологія» / А. І. Гарбут. - Одеса : НУ «ОЮА», 2025. – 46 с.
Keywords: стрес; жінки; воєнний стан